2020
DOI: 10.1186/s12904-020-00593-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and health related quality of life in a population with advanced chronic obstructive pulmonary disease, a cross-sectional study

Abstract: Background: It is important to understand the total burden of COPD and thereby be able to identify patients who need more intensive palliative care to avoid deteriorated quality of life. The aim of this study was to describe the psychosocial and demographic characteristics of a population with advanced COPD in a stable phase of the disease. Methods: This study was cross-sectional based on a prospective observational cohort. The following questionnaires were administered: Chronic Respiratory Disease Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…With the progress of COPD, the quality of life of patients gradually declines. 28,29 Several factors may contribute to poor quality of life in COPD patients including respiratory symptoms, exercise limitations. 30 In this meta-analysis, SF-36 and CCQ was used to evaluate the effects of singing on COPD patients, and the results showed that the singing group was significantly better than the control group in terms of quality of life physical component score.…”
mentioning
confidence: 99%
“…With the progress of COPD, the quality of life of patients gradually declines. 28,29 Several factors may contribute to poor quality of life in COPD patients including respiratory symptoms, exercise limitations. 30 In this meta-analysis, SF-36 and CCQ was used to evaluate the effects of singing on COPD patients, and the results showed that the singing group was significantly better than the control group in terms of quality of life physical component score.…”
mentioning
confidence: 99%
“…The standard of care at the outpatient clinic at Copenhagen University Hospital—North Zealand focuses on basic palliative care for individuals with severe COPD. The structure of the outpatient care program is designed to be able to respond to the individual and changing needs of the patients and it has resulted in improved HRQoL [ 52 ]. However, despite the patient-centered approach with an increased focus on individual palliative needs, these patients still have impaired HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…In this large international study, we have developed a digital voice-based biomarker for monitoring of RQoL using a combination of standard self-reported clinical information and voice-related features. We have shown that voice brings complementary information to improve the performances of the predictive model and increase the reliability of screening RQoL has been evaluated from socio-demographic and clinical factors in various respiratory diseases, but mainly focusing on a single disorder, such as COPD [30], [31], asthma [32], idiopathic pulmonary fibrosis [33], or COVID-19 [34]. There were also attempts to investigate the effect of several respiratory diseases simultaneously on RQoL by using a multicasecontrol design, where the use cases were COPD, asthma, allergic and non-allergic rhinitis [35].…”
Section: Discussionmentioning
confidence: 99%
“…MLP was composed of two hidden layers with 256 neurons each and a ReLU activation function, followed by dropout layers for preventing overfitting with a dropout rate equal to 0.3, and an output layer with a sigmoid activation function is utilized in this paper. We used Adam optimizer, binary cross entropy loss function, batch size equal to 32, while the optimal learning rate (0.0001) and the number of epochs (30) are determined via grid search. Note that Adam has an adaptive per-parameter learning rate, which is computed using the initial learning rate as an upper limit.…”
Section: E Rqol Predictionmentioning
confidence: 99%